Effective vulnerability management managing risk in the vulnerable digital ecosystem - Hughes, Chris; Robinson, Nikki (John Wiley & Sons, Inc., 2024)
Infuse efficiency into risk mitigation practices by optimizing resource use with the latest best practices in vulnerability management Organizations spend tremendous time and resources addressing vulnerabilities to their technology, software, and organizations. But are those time and resources well spent? Often, the answer is no, because we rely on outdated practices and inefficient, scattershot approaches. Effective Vulnerability Management takes a fresh look at a core component of cybersecurity, revealing the practices, processes, and tools that can enable today's organizations to mitigate risk efficiently and expediently in the era of Cloud, DevSecOps and Zero Trust. Every organization now relies on third-party software and services, ever-changing cloud technologies, and business practices that introduce tremendous potential for risk, requiring constant vigilance. It's more crucial than ever for organizations to successfully minimize the risk to the rest of the organization's success. This book describes the assessment, planning, monitoring, and resource allocation tasks each company must undertake for successful vulnerability management. And it enables readers to do away with unnecessary steps, streamlining the process of securing organizational data and operations. It also covers key emerging domains such as software supply chain security and human factors in cybersecurity. Learn the important difference between asset management, patch management, and vulnerability management and how they need to function cohesively Build a real-time understanding of risk through secure configuration and continuous monitoring Implement best practices like vulnerability scoring, prioritization and design interactions to reduce risks from human psychology and behaviors Discover new types of attacks like vulnerability chaining, and find out how to secure your assets against them Effective Vulnerability Management is a new and essential volume for executives, risk program leaders, engineers, systems administrators, and anyone involved in managing systems and software in our modern digitally-driven society.
Description based on online resource; title from digital title page (viewed on April 11, 2024)
Keywords: Computer security; Sécurité informatique